Utilization of the library recreational function through the Gasibu Library Bandung - Anwar, Rully Khairul; Agustine, Merryam (Record and Library Journal, 2021)
Background of the study: One of the capabilities of the library is to provide pleasant conditions for relaxation that cannot be found at home. This research has the background to find out more about the recreational functions of public libraries through the Gasibu Bandung library which is located around the Gasibu field. Purpose: The purpose of this study is divided into two parts, namely to determine the recreational function of the library as a means of channeling reading hobbies and to find out the Gasibu library as a tourism developer of Bandung city. Method: The technique used in this research is a qualitative research technique with a case study method. Findings: The results of this study indicate that the Gasibu library is an appropriate informative recreation facility to serve as a means of channeling people's reading hobbies and the Gasibu library can add to the tourist attraction of Bandung city because of the uniqueness of the information center in the middle of recreational facilities. Conclusion: In fulfilling the recreational needs of its users, the Gasibu library is carried out by providing books that are suitable for its purpose. Novels and other literary forms, works of art, travel books, biographies, popular magazines, especially other recreational books. The Gasibu library building is also the main attraction because of its location in the middle of recreational facilities.